A distributed MILP framework to coordinate restoration of transmission and distribution systems under imperfect communication - Lizhou Jiang; Binye Ni; Xinlei Cai; Jinzhou Zhu; Longteng Wu; Tianyang Zhao; Gengfeng Li (International Journal of Electrical Power & Energy Systems)
This paper proposes a novel distributed framework to restore transmission and distribution systems (T&DS) under imperfect communication. First of all, nodal reserve is introduced into the power exchange constraint, thereby making the coordination between transmission systems (TS) and distribution systems (DS) more efficiently to achieve. However, the above formulation undermines the convexity of the model since constraints regarding reserve response involve bi-linear terms. In this regard, a novel linearization method, with guaranteed accuracy and limited complexity, is proposed to reformulate the coordinated model into a mixed-integer linear programming problem. To solve this problem, a primal decomposition-based distributed framework is developed. Then, this paper takes imperfect communication into consideration and adopts data prediction methods to encounter this kind of issue. We theoretically prove that the distributed framework is guaranteed to converge under imperfect communication with the proposed strategy. Finally, the effectiveness and scalability of the proposed framework are verified by numerical experiments.